2013
DOI: 10.5423/ppj.oa.11.2012.0176
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biological Control of Phytophthora Blight of Pepper by Biosurfactant-Producing Pseudomonas

Abstract: Pseudomonas isolates from different crop plants were screened for in vitro growth inhibition of Phytophthora capsici and production of biosurfactant. Two in vivo experiments were performed to determine the efficacy of selected Pseudomonas strains against Phytophthora blight of pepper by comparing two fungicide treatments [acibenzolar-S-methyl (ASM) and ASM + mefenoxam]. Bacterial isolates were applied by soil drenching (1 × 109 cells/ml), ASM (0.1 μg a.i./ml) and ASM + mefenoxam (0.2 mg product/ml) were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…B. mojavensis isolated from diverse environments have been reported to have significant activity against phytopathogens also (Özyilmaz and Benlioglu 2013). But B. mojavensis BmB 4 isolated in the study was not found to have any activity against phytopathogens when it was tested and it might have specialised for broad antibacterial activity as part of its endophytic adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…B. mojavensis isolated from diverse environments have been reported to have significant activity against phytopathogens also (Özyilmaz and Benlioglu 2013). But B. mojavensis BmB 4 isolated in the study was not found to have any activity against phytopathogens when it was tested and it might have specialised for broad antibacterial activity as part of its endophytic adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Different lowercase letters above the bars indicate significant difference between the treatments at P < 0.05 level by ttest Many studies reported that the application of Bacillus spp., such as B. subtilis, B. cereus, Bacillus licheniformis, could manage diseases caused by Phytophthora species, such as Phytophthora capsici, P. sojae, Phytophthora fragariae var. fragariae, Phytophthora infestans, and Phytophthora cactorum on pepper, soybean, potato, cucumber, alfalfa, strawberry and apple (Utkhede 1984;Handelsman et al 1990;Osburn et al 1995;Anandhakumar and Zeller 2008;Özyilmaz and Benlioglu 2013;Maksimov et al 2014;Khabbaz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…tritici on wheat (Thomashow and Weller 1988), Ralstonia solanacearum on tomato (Barret et al, 2009), stem rot disease caused by Phytium spp on cotton (Erdoğan, Bölek, & Göre, 2016). The combination of Pf and B. subtilis was able to reduce Plasmodiophora brassicae on chinese cabbage (Zhao et al, 2016) and Phytopthora capsici in pepper (Özyilmaz & Benlioglu, 2013). (Table 2 and Table 3) reflected to the more plants having qualified physical appearance.…”
Section: Plant Growth Improvement and White Rust Incidencementioning
confidence: 99%